1997
DOI: 10.1046/j.1365-2362.1997.2230757.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased nitric oxide production in collagenous and lymphocytic colitis

Abstract: The production of nitric oxide (NO) is increased in active ulcerative colitis and in Crohn's disease. We have studied NO production in collagenous colitis (CC) and lymphocytic colitis (LC), both of which are inflammatory bowel disorders of unknown aetiology. NO levels were measured directly in gas sampled from the colon during colonoscopy. Plasma levels of NO metabolites (nitrate/nitrite) were also measured. Luminal NO levels were more than 100 times higher in patients with CC compared with controls. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 16 publications
(20 reference statements)
2
47
0
Order By: Relevance
“…Colonic NO production is greatly increased in active MC caused by upregulation of inducible nitric oxide synthase (iNOS) in the colonic epithelium [66][67][68][69] . A major transcriptional inducer of iNOS gene expression is the transcription factor nuclear factor-κB (NF-κB).…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…Colonic NO production is greatly increased in active MC caused by upregulation of inducible nitric oxide synthase (iNOS) in the colonic epithelium [66][67][68][69] . A major transcriptional inducer of iNOS gene expression is the transcription factor nuclear factor-κB (NF-κB).…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…A novel minimally invasive technique for measurement of NO levels in the rectum has been developed. By this technique, increased rectal NO levels have been shown in patients with intestinal inflammatory disorders such as ulcerative colitis, Crohn's disease, collagenous colitis, and celiac disease (7,8,16,19). We have recently shown that rectal NO levels are greatly increased in patients with infectious gastroenteritis, including Clostridium difficile-associated diarrhea (CDAD) (9).…”
mentioning
confidence: 99%
“…A potential protective role of NO in human IBD is supported by the findings of higher colonic NO induction in patients with collagenous colitis, a process with scarce inflammatory infiltration and absence of mucosal damage, than in ulcerative colitis (Lundberg et al, 1997). Although ulcerative colitis and collagenous colitis are distinct disorders, with differing etiopathogenesis, the lower NO concentrations observed in active ulcerative colitis compared with collagenous colitis may reflect impaired compensatory NO production by iNOS, in a condition characterized by increased formation of oxidant radicals.…”
Section: Salas Et Almentioning
confidence: 95%